Sistem Penataan Arsip Dalam Menunjang Kelancaran Pelayanan Publik Pada Kantor Camat Poasia Kota Kendari - Aprillia, Rini; Alam, Syamsul; Rahman, Rahman (Universitas Halu Oleo, 2020)
The archive arrangement system is a process of systematically arranging files or archives to facilitate re-discovery whenever needed. The purpose of this study was to determine the archival structuring system to support the smooth running of public services at the Head Office of Poasia, Kendari City. This research approach is qualitative. The data collection techniques used were documentation and interviews, the informants of this study were 3 people. The results of this study indicate that the archive arrangement system at the sub-district office of Poasia applies by date and by subject matter. Existing services at the Poasia Sub-district Office are Deed of Sale and Purchase of Land, Making Business Permits and Receiving Letters.